The prospects for the protection of civilian population in Poland in the conditions of a potential armed conflict - Adamkiewicz, Jakub (Scientific Journal of Bielsko-Biala School of Finance and Law, 2023)
One of the fundamental tasks of state institutions in conditions of armed conflict is the protection of the population. In the light of international and national law, this task is dealt with in Poland by the Civil Defence of the Country. The aim of the article is to present the condition of this organisation and to assess its ability to fulfil the assigned mission. Conclusions are drawn on the basis of NIK reports and own empirical research.